Enhancing Security, Sustainability and Resilience in Energy, Food and Water - Sojamo, Suvi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book looks at the ways that energy, food, and water help to create connections between sustainability and security. The concept of security is in our current societies increasingly connected with sustainability, which seeks to ensure that we as humans are able to live and prosper on this planet now and in the future. The concepts of energy security, food security, and water security-used separately or together-manifest the burgeoning linkages between security and sustainability. This book brings together ten scientific articles that look at different aspects of security, sustainability, and resilience with an emphasis on energy, food, and/or water in the context of Finland and Europe. Together, the articles portray a rich picture on the diverse linkages between both energy, food, and water, and between security and sustainability. In sum, the articles and related preface conclude that ensuring sustainable security-or secure sustainability-requires systemic, structured processes that link the policies and actors in these two important but still distant fields.